TARBIYACHILAR EKALOGIK SAVODXONLIGINING BOLALAR HAYOTIDAGI AHAMIYATI. - Usarova Muborak Xabibulla qizi; Obidova Dilnoza Faxriddin qizi (TADQIQOTLAR, 2025)
Abstract This article discusses how the well-developed environmental education and upbringing of educators contributes to the proper development of children’s environmental education and upbringing, and is the first step taken by the younger generation towards achieving environmental sustainability.